2020
DOI: 10.3390/su12072747
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Balance under Organic Amendments in the Wheat-Maize Cropping Systems of Sloppy Upland Soil

Abstract: With an increasing interest in closing the nutrient loop in agroecosystems, organic amendments are highly recommended as a reliable resource for soil nutrient recycling. However, from a carbon sequestration perspective, not much has been reported on the contribution of different organic amendments to soil organic carbon (SOC), crop carbon (C) uptake, and soil carbon dioxide (CO2) emissions in wheat-maize cropping systems of sloppy upland soil. To fill the knowledge gap, a two-year lysimeter-field plots experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 57 publications
(101 reference statements)
0
0
0
Order By: Relevance
“…All treatments showed an increase in germination, plant height, dry matter content and yield when compared to the respective control. Badar, et al [80] observed that soil salinity can decrease crop growth, metabolism, and the quality of the produce, with salinity causing a decrease in root length of up to 36%, which significantly increased (up to 80%) when organic wastes were applied; similar findings were reported by Rop, et al [81] and Bah, et al [82]. Other authors observed that addition of gypsum and organic amendments compensated for deficiencies in both soil micro-and macronutrients during and after soil reclamation [66].…”
Section: Impacts Of Soil Restoration On Plant Growth Physiology and Y...supporting
confidence: 64%
“…All treatments showed an increase in germination, plant height, dry matter content and yield when compared to the respective control. Badar, et al [80] observed that soil salinity can decrease crop growth, metabolism, and the quality of the produce, with salinity causing a decrease in root length of up to 36%, which significantly increased (up to 80%) when organic wastes were applied; similar findings were reported by Rop, et al [81] and Bah, et al [82]. Other authors observed that addition of gypsum and organic amendments compensated for deficiencies in both soil micro-and macronutrients during and after soil reclamation [66].…”
Section: Impacts Of Soil Restoration On Plant Growth Physiology and Y...supporting
confidence: 64%